(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The provision of cooperative education, without doubt, is a major determinant for the success of agricultural cooperative business especially in developing countries like Nigeria, where cooperatives are used as a strategy in the development process. This study is aimed at assessing the provision of cooperative education among agricultural cooperative business owners for success of their business in Anambra State. 50 cooperative administrators were purposively sampled from the Management Committees of Agricultural Cooperative Business and District Cooperative Officers (DCO’s) in the twenty one local government areas of Anambra State for the study. Two research questions guided the study. Data were collected with structured questionnaire which was analyzed using percentages and mean scores. The findings of the study revealed low provision of cooperative education by the government and the cooperatives themselves. The findings also revealed bare provisions by non-governmental and international bodies. It was recommended among others that government and nongovernmental bodies that provide financial support to agricultural cooperative business in Nigeria should set aside some percentage of the funds provided for education of the cooperative members. This is to ensure effective use of such funds